"Because everything changes that day; you don't do the routine": Alterations and activities chronically ill women undertake on days with health care provider appointments. (December 2015) - Crooks, Valorie A
Objectives: Research points to the importance of interactions with health care providers for chronically ill patients. Meanwhile, we know little about how visits to providers' offices are accommodated in these patients' lives. This analysis identifies the full scope of routine alterations and preparatory activities that require chronically will women's time and energy specifically on appointment days . Methods: 55 semi-structured interviews were conducted with women with fibromyalgia syndrome living in Ontario, Canada. Interviews were transcribed verbatim and analyzed using the constant-comparative technique. Results: Two trajectories are identified: (1) alterations to daily routines on appointment days; and (2) activities to prepare for the provider–patient interaction. Factors such as wanting to minimize symptom exacerbation, desires to come across as informed patients, limited time afforded to interactions, and access to transportation explain why these particular routine alterations and preparatory activities were undertaken. Discussion: Findings demonstrate that the health care provider–patient interaction does not start or end in the space of the provider's office but is, rather, an event that is part of a larger process primarily focused on its successful negotiation. This suggests that the boundaries of the appointment need to be reconsidered, which holds implications for appointment-focused interventions aimed at chronically ill patients.